ADMINISTRASI PELAYANAN PENERBITAN SURAT IZIN PENANGKAPAN IKAN PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI UTARA - DJUNNA, HARISMAN; POSUMAH, JOHNNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
This study is about the administration of the service of issuing permits for fishing in the marine and fisheries service of North Sulawesi Province. Public service regulations that are still scattered in the number of regulation that are sectoral, making public services in Indonesia are in a conditional that is not yet manageable. In other words the community has not received the excellent service that was their hope. In order to know the quality of service that is felt significantly by consumers, there are indicators of consumer satisfaction measures that lie in the five dimensions of service quality. 1). Tangibles : Service quality in the from of physical facilities, offices, computerized administration, waiting room, information places. 2). Reliability : The ability and reliability to provide trusted service. 3). Responsivess : The ability to help and provide services quickly and accurately, as well as being responsive to consumer desires. 4). Assurance : The ability and friendliness as well as the courtesy of employees in convincing consumer trust. 5). Emphaty : Firm but attentive attitude of employees toward consumers. In this study the authors used a qualitative approach with descriptive analysis techniques, in this study primary data were obtained from interview and could also be from the result of questionnaires, while secondary data were obtained from documents from either the relevant agencies or other relevant agencies. The result have not been able to optimally meet the needs of the service user community. Researchers provide advice on this is about these five aspects : 1). Tangibles aspects : updating both the quality and quantity of facilities or infrastructure available at the maritime and fisheries service office in North Sulawesi Province. 2). Reliability aspects : Strive for the ability and reliability of officers to the provide services by attending training, both internal and external. 3). Responsiveness aspects : Every service officer or apparatus at the North Sulawesi Province’s Office of maritime affairs and fisheries must try to increase understanding quickly and precisely on what is the problem of service needs desired by the community. 4). Assurance aspects : each service officer must improve attitudes towards all citizens who need service. 5). Emphaty aspects : every officer is required to have firmness in carrying out their duties and responsibilities. Keywords : Administration, Service, Fishing License.